2020
DOI: 10.1101/2020.02.20.957068
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Differential Disease Severity and Whole Genome Sequence Analysis for Human Influenza A/H1N1pdm Virus in 2015-2016 Influenza Season

Abstract: 39During the 2015-16 winter, the US experienced a relatively mild influenza season compared to Taiwan 40 which had a large number of total and severe cases. While H1N1pdm viruses dominated global 41 surveillance efforts in this season, the global distribution of genetic variants and the contribution of 42 genetic to disease severity has not been investigated. Nasal samples collected from influenza A positive 43 patients by the Johns

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…We found a wide diversity of A(H1N1)pdm09 strain variants in concurrent circulation, mainly within antigenic drift clades 6B.1 and 6B.2. Clade 6B.1 and 6B.2 A(H1N1)pdm09 viruses became dominant in 2015/16 across the world, including Europe, and were associated with increased hospital admissions and more severe disease in clinical cases [8,10,19,28,38]. The 6B.1 clade dominated human cases in the 2015/16 influenza season in Europe, a pattern we observed by the sequence analysis of Ukrainian A(H1N1)pdm09 strains (Figure 2).…”
Section: Discussionmentioning
confidence: 54%
See 3 more Smart Citations
“…We found a wide diversity of A(H1N1)pdm09 strain variants in concurrent circulation, mainly within antigenic drift clades 6B.1 and 6B.2. Clade 6B.1 and 6B.2 A(H1N1)pdm09 viruses became dominant in 2015/16 across the world, including Europe, and were associated with increased hospital admissions and more severe disease in clinical cases [8,10,19,28,38]. The 6B.1 clade dominated human cases in the 2015/16 influenza season in Europe, a pattern we observed by the sequence analysis of Ukrainian A(H1N1)pdm09 strains (Figure 2).…”
Section: Discussionmentioning
confidence: 54%
“…To understand the genetic basis for the severity of ILI and SARI in Ukraine, we conducted molecular genetics and phylogenetics analyses of A(H1N1)pdm09 influenza viruses from SARI cases that circulated in Ukraine during the 2015/16 epidemic season. We found that most of the A(H1N1)pdm09 influenza viruses circulating in Ukraine were of the H1 6B.1 lineage that became predominant worldwide and was associated with antigenic escape from immunity [7][8][9][10]. Our study also revealed the emergence of new genotypic variants in Ukraine, containing unique amino-acid substitutions in HA, NS1, and other viral genes.…”
Section: Introductionmentioning
confidence: 54%
See 2 more Smart Citations
“…After the novel influenza A/H1N1 virus (H1N1pdm09) emerged in 2009, it supplanted previous human H1N1 viruses to become a seasonal human H1N1 virus. 6 It is unknown how circulation of novel influenza viruses affects influenza seasonality. Therefore, to improve the current vaccination strategy, which was formulated with national 2005-2011 influenza seasonality in mind, it is useful for public health policy makers to understand important changes in influenza seasonality during the most recent decade.…”
Section: Introductionmentioning
confidence: 99%